(untitled) (Biological Sciences - PJSIR, 2003)
!lea\’)’ mc1alsconccnlrntions in the wntcr and sediment al four /.Ones on the IO er Ikpoba river in Bemn City, Nigeria ere investigated b) using the flame atomic absorption spectrophotomclry technique. Mean conce111ra1ions (i1g’l) were as Cd (0.73), Cr (0.40), Cu ( 1.30). I e (4.00). Pb (0.90). Mn C:l.l 0). Ni (2.05) and Ln (1.20). Mean melHI concentrations (µg_g dry ) in th,: sediment sample,; ere as follows:Cd (1.50). Cr (0.90). Cu (1.90), Fe (7.90). Pb (J.JO).Mn (4.60). Ni (3.95) and Zn (4.70).Conccnlfations were of Cd and Pb ater exceeded the: hmils recommended by WI 10 for portable drinking water. [he metal concen1ra1ions 111 the nvcr water , ere higher during the dry seasons in all the1.oncs hen ater as used in greater demand by 1c urban population. there wasno signi1ican1 difference (P 0.05) between th.: concentrations of metals in the ri, er ater during the dry and rainy season 111 lhe months of sampling.